2018
DOI: 10.5539/esr.v7n2p14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Simplified Dynamic Wave, Diffusion Wave and the Full Dynamic Wave Flood Routing Models

Abstract: The accuracy of prediction and ease of use of the three popular flood routing models; simplified dynamic Wave, diffusion wave, and full dynamic wave were evaluated. The models were evaluated along a reach of the Credit River Watershed, in Southern Ontario, Canada. The simplified dynamic wave model showed better accuracy and easier formulation when compared against the diffusion wave and the full dynamic wave models. Indicating that the simplified dynamic wave model can be applied to reaches where the diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…= 0.0543 0.5 −0.5 (5) This formula was developed from the study of 19 sub-basins, located in Scioto and Sandysky (Ohio) area. The area of the basin must be between 65 to 4,206 2 .…”
Section: Kirpich's Model [11]mentioning
confidence: 99%
See 2 more Smart Citations
“…= 0.0543 0.5 −0.5 (5) This formula was developed from the study of 19 sub-basins, located in Scioto and Sandysky (Ohio) area. The area of the basin must be between 65 to 4,206 2 .…”
Section: Kirpich's Model [11]mentioning
confidence: 99%
“…[1,2]. According to some authors, the time of concentration can be defined as the time that a single drop of water takes to travel from the most distant point in the basins to the point of exit [3][4][5][6][7][8]. Following [3], this parameter is related to the lines of equal time of flow to the outlet, called isochrones representing the grown of contributing area to the streamflow outlet after certain time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over seven million people have lost their lives in floods between 1990 and 2017 in Asia alone [1,2]. Predicting flood water levels, the design of stable alluvial channels, and protecting lives and properties during major flood events is one of the greatest challenges of the 21st century [3,4]. Open channel levees are used extensively in hydraulic and environmental engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most popular approach for determining T c is the NRCS velocity method. Past experience and previous studies have shown that the NRCS velocity method is considered to be the most accurate method for estimating T c for both rural and urban catchments (McCuen et al, 1984;Fang et al, 2008;Sharifi and Hosseini, 2011;Perdikaris et al, 2011Perdikaris et al, & 2018. This is primarily due to the fact that the velocity method is based on hydraulic principles, and as a result is more reliable than purely empirical equations.…”
mentioning
confidence: 99%